A tale of two bridges: Factors influencing career choices of trainee nursing associates in England: A longitudinal qualitative study. Issue 5 (5th June 2022) - King, Rachel Louise; Taylor, Bethany; Laker, Sara; Wood, Emily; Senek, Michaela; Tod, Angela; Ryan, Tony; Snowden, Sally; Robertson, Steven
Abstract: Aim: The nursing associate role has created a new second‐level nursing role and provided an alternative route into registered nursing. For some, this provides a previously inaccessible opportunity for career progression. The aim of the study was to understand the factors that influence career choices of trainee nursing associates. Design: A longitudinal qualitative study of trainee nursing associate motivations, experiences and career aspirations. Methods: Semi‐structured interviews with trainee nursing associates from across England, UK, in February 2020 ( N  = 14) and March 2021 ( N  = 13). Diary data were also collected. Interview and diary data were analysed thematically. Reporting has followed COREQ guidelines. Results: Nursing associate training was viewed by some as a bridge into registered nursing. Role ambiguity led several to seek perceived security offered by the Registered Nurse profession. Those preferring to remain as nursing associates were keen to embed the bridging role between healthcare assistants and Registered Nurses, valuing a positive workplace culture.